1996
DOI: 10.1111/j.1600-0714.1996.tb00278.x
|View full text |Cite
|
Sign up to set email alerts
|

Salivary cortisol and anxiety in recurrent aphthous stomatitis

Abstract: Anxiety and salivary cortisol were measured in two groups of patients with recurrent aphthous ulceration. One group of patients had persistent aphthae (Group 1) and the others had been relieved of their aphthae following correction of detected haematinic deficiency states (Group 2). Anxiety was measured using the Hospital Anxiety and Depression scale and radioimmunoassay of salivary cortisol. There was a statistically significant increased proportion of borderline or clinically anxious patients in Group 1 comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
80
2
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 23 publications
9
80
2
3
Order By: Relevance
“…Nevertheless, many patients make an association between RAS and what they term stress. It has been reported that previous studies have focused on individuals who in retrospect were more likely to have had trait anxiety as a basis for their perceived stress (McCartan et al 1996). Trait anxiety is nearly equivalent to stress and can be measured, although the biochemical response to both may differ.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, many patients make an association between RAS and what they term stress. It has been reported that previous studies have focused on individuals who in retrospect were more likely to have had trait anxiety as a basis for their perceived stress (McCartan et al 1996). Trait anxiety is nearly equivalent to stress and can be measured, although the biochemical response to both may differ.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study investigated the possible association between anxiety, as measured by Hospital Anxiety and Depression scale (HAD), and salivary cortisol in patients with RAS, concluding that stress may play a role in the etiology of RAS (McCartan et al 1996).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some changes in salivary composition, such as pH, that affect the local properties of saliva and a stress-induced rise in salivary cortisol have been correlated with RAS 17,18 . Although direct association of salivary gland dysfunction with RAS has not been demonstrated 19 , patients with a combination of RAS and xerostomia may experience increased symptoms due to the increased oral dryness.…”
Section: Local Factorsmentioning
confidence: 99%